Neo-Sufistic Economic Empowerment: Reconstruction of the Islamic Economic Paradigm Through the Qadiriyyah Wa Naqsyabandiyyah Order of Berjan Purworejo - Sahlan; Ahmad Rofiq; Mahsun (Sharia Economic and Management Business Journal (SEMBJ), 2026)
This study examines the role of neo-Sufism in reconstructing the paradigm of Islamic economics through the economic empowerment practices of the Qadiriyyah wa Naqsyabandiyyah Order in Berjan Purworejo, Indonesia. Using a qualitative case-study approach, data were collected through in-depth interviews, participant observation, and documentation involving four imams, twenty badal tarekat, and fifty active members of the order. The findings reveal that spiritual practices within the congregation function not only as religious rituals but also as productive social forces shaping economic behavior, collective ethics, and community resilience. Żikr, tawakkal, ukhuwah, and barakah orientation were found to generate work discipline, trust-based economic relations, anti-consumerist attitudes, and solidarity-driven economic networks among members. The study further demonstrates that the congregation operates as a community-based economic ecosystem grounded in spiritual trust and moral commitment. This research formulates the Neo-Sufistic Economic Empowerment Theory, which positions spirituality as productive spiritual capital capable of strengthening economic resilience and communal empowerment. The study also critiques the contemporary Islamic economic paradigm for being overly formalistic, finance-oriented, and lacking spiritual dimensions, while proposing a more humanistic, solidarity-based, and transformative model of Islamic economic development.